ELECTRO-OPTICAL SWITCHING OF THE MAIN OPTICAL AXIS OF A FERROELECTRIC LIQUID CRYSTAL SPIRAL NANOSTRUCTUREIN A PLANAR-ORIENTED DISPLAY CELL - E. P. Pozhidaev; T. P. Tkachenko; A. V. Kuznetsov; I. N. Kompanets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
In a known display cell with the nematic liquid crystal (NLC) and interdigital electrodes on one of the glass substrates, the “In-Plane Switching” (IPS) mode is implemented, in which the NLC main optical axis reorients in a plane parallel to substrates, providing the most correct color reproduction at different angles view, up to 178 ° horizontally and vertically. Unfortunately, the creation of interdigital metal electrodes complicates and increases the technological process cost and causes a decrease in image contrast. At the same time, experimental results and calculations based on classical electro-optics of crystals indicate that electrooptical switching in the IPS mode is a natural and intrinsic feature of a conventional (with continuous electrodes) display cell with a planar-oriented layer of the ferroelectric liquid crystal (FLC), in which the effect of the deformed (by the electric field) helix FLC nanostructure is realized (DHF effect). In such a cell, the reorientation of the main optical axis under the influence of a weak electric field also occurs in the substrate plane if the FLC has a small pitch (about 100 nm or less) and a large tilt angle of molecules in the layer (about 38 ° or more). The dependences of the FLC cell light transmittance measured in this work, confirmed the achievement of the IPS electro-optical mode in the DHF FLC cell; moreover, the light modulation frequency was 1 kHz. Thus, while maintaining all the advantages of the IPS mode known in NLC, its implementation in FLC allows additionally obtaining technological advantages and multiple increase in modulation frequency.